An automated technique for double staining of bone and cartilage in fetal mouse skeletal specimens using alizarin red S and Alcian blue. (3rd April 2022) - Booth, Matthew; Powell, Nancy; Corfield, Clare; French, Julian M.
ABSTRACT: Automated methods exist for double staining bone and cartilage in fetal rat, rabbit and mice using alizarin red S and Alcian blue. None of the published methods produce consistently stained bone and cartilage in mouse fetuses. Consequently, we modified an automated staining method for use with mouse fetuses. Methanol replaced 95% industrial denatured alcohol, and 5% glacial acetic acid was used instead of 20%. We describe here our new protocol, which has been used successfully to stain specimens for regulatory prenatal developmental toxicity studies.